DETERMINATION OF ORIENTATION PARAMETERS AND AUTOMATIC WIND WHEEL SPEED CONTROL - Nurkimbayev, Sagynysh; Shumeiko, Ivan; Kassenov, Assylbek; Itybaeva, Galya (Journal of Applied Engineering Science, 2024)
The design of the wind wheel and storm protection will help greatly improve the performance and safety of the wind-powered water-lifting unit. This, in turn, will contribute to improving the quality of life of rural residents. The authors of this study developed the design of a wind-powered water-lifting unit. The research aims to develop a wind-powered water-lifting unit with a capacity of up to 2.5 m3/hour, resistant to hurricane gusts of wind, with automatic control of wind wheel speed. The mathematical expressions used consider the force of the airflow and the screen area of the side blade, which takes the plane of the wind wheel out of the wind when it increases to values above the permissible operating wind speed. Numerical methods were used to calculate the forces on the spring returning the wind wheel plane to the initial position at different wind speeds. The dependences of the effect of airflow velocity on the free rotation of the wind wheel, i.e., without its running out of the wind, have been determined.